Effect of Inhaled Nebulized Furosemide (40 and 120 mg) on Breathlessness during Exercise in the Presence of External Thoracic Restriction in Healthy Men - Waskiw-Ford, Marcus; Wu, Anne; Mainra, Amar; Marchand, Noah; Alhuzaim, Abdullatif; Bourbeau, Jean; Smith, Benjamin M.; Jensen, Dennis (Frontiers in Physiology, 2018)
Inhalation of nebulized furosemide has been shown to alleviate breathlessness provoked experimentally in health and disease; however, it remains unclear whether the efficacy of nebulized furosemide on breathlessness is dose-dependent. We tested the hypotheses that inhaled nebulized furosemide would be associated with a dose-dependent relief of breathlessness during exercise testing in the setting of abnormal restrictive constraints on tidal volume (VT) expansion. In a randomized, double-blind, crossover study, twenty-four healthy men aged 25.3 ± 1.2 years (mean ± SE) completed a symptom-limited constant-load cycle endurance exercise test in the setting of external thoracic restriction via chest wall strapping to reduce vital capacity by ~20% following single-dose inhalation nebulized furosemide (40 mg and 120 mg) and 0.9% saline. Compared with 0.9% saline, neither 40 mg nor 120 mg of inhaled nebulized furosemide had an effect on ratings of perceived breathlessness during exercise or an effect on cardiometabolic, ventilatory, breathing pattern or dynamic operating lung volume responses during exercise. Urine production rate, the percentage of participants reporting an “urge to urinate” and the intensity of perceived “urge to urinate” were all significantly greater after inhaling the 120 mg furosemide solution compared with both 0.9% saline and 40 mg furosemide solutions. We concluded that, under the experimental conditions of this study, inhalation of nebulized furosemide at doses of 40 mg and 120 mg did not alleviate breathlessness during exercise in healthy men.